2002
DOI: 10.1152/ajpregu.2002.282.1.r295
|View full text |Cite
|
Sign up to set email alerts
|

Increased coronary blood flow signals growth of coronary resistance vessels in near-term ovine fetuses

Abstract: We measured maximal coronary artery conductance in near-term fetal sheep before and after chronic infusion with adenosine to determine whether an increase in coronary flow without hypoxemia results in increased coronary vascular growth. Adenosine was infused into the circumflex coronary artery for 12 h each day for 4 days. Coronary flow was maintained at double the resting level by regulating the infusion of adenosine via a computerized servocontrol device signaled by a Doppler flow-velocity sensor. Total arte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…Many studies have demonstrated that chronic elevation of tissue adenosine concentrations induced by the adenosine reuptake blocker dipyridamole (Adolfsson et al 1981, 1982; Adolfsson 1986a, b; Belardinelli et al 2001; Mall et al 1987; Mattfeldt and Mall 1983; Symons et al 1993; Tornling et al 1978, 1980a, b; Tornling 1982a, b; Torry et al 1992), or long-term administration of adenosine and its analogs (Hudlicka et al 1986; Wothe et al 2002; Ziada et al 1984), promotes capillary proliferation in the heart and skeletal muscles. Antagonism of ARs with caffeine abrogated VEGF upregulation in skeletal muscles induced by local injection of adenosine 5′- N -ethyluronamide (NECA) into the mouse hind limb and produced a 46% reduction in neovascularization in a mouse ischemic hind limb model (Ryzhov et al 2007).…”
Section: Role Of Adenosine In Neovascularizationmentioning
confidence: 99%
“…Many studies have demonstrated that chronic elevation of tissue adenosine concentrations induced by the adenosine reuptake blocker dipyridamole (Adolfsson et al 1981, 1982; Adolfsson 1986a, b; Belardinelli et al 2001; Mall et al 1987; Mattfeldt and Mall 1983; Symons et al 1993; Tornling et al 1978, 1980a, b; Tornling 1982a, b; Torry et al 1992), or long-term administration of adenosine and its analogs (Hudlicka et al 1986; Wothe et al 2002; Ziada et al 1984), promotes capillary proliferation in the heart and skeletal muscles. Antagonism of ARs with caffeine abrogated VEGF upregulation in skeletal muscles induced by local injection of adenosine 5′- N -ethyluronamide (NECA) into the mouse hind limb and produced a 46% reduction in neovascularization in a mouse ischemic hind limb model (Ryzhov et al 2007).…”
Section: Role Of Adenosine In Neovascularizationmentioning
confidence: 99%
“…Capillary proliferation and recruitment of the coronary microcirculation likely contribute to this response (20,24). Although vascular endothelial growth factor (VEGF) has been suggested to stimulate increased myocardial vascularization in the chronically anemic ovine fetus, other angiogenic agents, including shear-stress-activated factors such as adenosine, are likely involved (2,24,42).…”
mentioning
confidence: 99%
“…Although we have no direct evidence to support this contention, venous pressures are Ϸ5 mm Hg higher and the rate-pressure product is greater in cord-compressed fetuses [controls, 7.92Ϯ0.75 versus UCC, 8.99Ϯ0.79 (beats/min per mm Hg)ϫ10 3 ], which may indicate the potential for greater cardiac preload and increased myocardial work, respectively. Estrogen 23 and adenosine 24,25 have been shown to increase coronary flow through induction of NO, which may aid greater cardiac work.…”
Section: Discussionmentioning
confidence: 99%